Avrupa Birliği eğitim politikaları ve bu politikalara Türk Eğitim Sistemi’nin uyumu - Topsakal, Cem (My University, 2003)
Bu çalışmada, Avrupa Birliği eğitim politikaları ve bu politikalara Türk Eğitim Sistemi'nin uyumu incelenmektedir. Araştırma beş bölümden oluşmaktadır: Girişte problem, amaç, önem, sınırlılıklar, tanımlar, yöntem ve ilgili araştırmalar ortaya konmuş, ikinci bölümde Avrupa Birliği'nin gelişimi ve Türkiye'nin Avrupa Birliği süreci verilmiştir. Üçüncü bölümde Avrupa Birliği eğitim politikaları saptanmıştır. Bu politikalar: Eğitim ve öğretim sistemlerinin amaçları/ eğitim plânlaması, öğretmen ve öğrencilerin üye ülkeler arası dolaşımı, diplomaların tanınması, yabancı dil öğrenimi ve öğretimi, okul eğitimi ve yükseköğretimde kalitenin geliştirilmesi, eğitim programları:1. Socrates, 2. Leonardo da Vinci, 3. Youth for Europe, yaşamboyu öğrenme, eğitim ve öğrenim alanında eğitim teknolojisinin kullanımı, bilgi ve iletişim teknolojileri konusunda öğretmenlerin eğitimi, istihdam ve eğitim, eğitim ve öğretimde işbirliği, yabancı düşmanlığı ve ırkçılık problemi, okulda güvenlik, Avrupa Birliği vatandaşlığı eğitimi. Dördüncü bölümde önemli bir politika olarak Avrupa Birliği kimliği/ vatandaşlığı ve eğitimi incelenmiştir. Beşinci bölümde bu politikalara Türk Eğitim Sistemi'nin uyumu Millî Eğitim Bakanlığı, Yüksek Öğretim Kurulu ve üniversiteler, hükümet düzeyi ve sivil toplum kuruluşları düzeylerinde ele alınmıştır. Araştırma

, sonuç, öneriler, ekler ve kaynakça ile sonlanmaktadır. Avrupa Birliği, Eğitim Politikaları, Avrupa Kimliği/ Vatandaşlığı, Türk Eğitim Sistemi, Uyum/ Entegrasyon. SUMMARY In this study, education politicy of European Union and the integration of Turkish Education System are investigated. The research consists of five parts: In the introduction part problem, aim, significance, limitation, definitions, method and related researches are presented, in the second part process of European Union and process of Turkey in terms of European Union are sown. In the third part, education policies of European Union are determined: Future objectives of education and trainig systems, mobility, action plan on basic skills and mobility, The obstacles to transnational mobility, academic recognition and professional recognition of qualifications in the community, improving and diversifying language learning and teaching within the education system of the European Union, early teaching of European Union languages, European Year of Languages 2001, school effectiveness, European cooperation in quality assurance in higher education, European report on quality of school education: sixteen quality indicators, second phase of the Community action programme Socrates, Leonardo Da Vinci, implementation of the youth programme,education and lifelong learning, education and employment, European cooperation in the field of education and training, information and communations tecnology and teachers trainig, response of educational systems to the problems of racism and xenophobia, safety at school. In the fourth part, as an important policy the identify/ citizenship and education of European Union are investigated. In the fifty part, the harmony with these policies and Turkish Education System are deal with in terms of level of Minister of Education, Higher Education Committee/ Institution (Yüksek Öğretim Kurulu/ Kurumu) and universities, goverment and non-governmental organizations. This research is finished with summary, conclusion, and proposals, adds and referances. Key Words: European Union, Education Politicies, Europe İdentify/ Citizenship, Turkish Education System, Harmonisation/ Integration.
Keywords: Eğitim